ANALISIS BEBAN KERJA BIDANG PENGELOLAAN SAMPAH DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU - Arischa, Suci; ", Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The idea of the realization of good governance through bureaucratic reform needs to be implemented. Bureaucratic reform is essentially an effort to reform and fundamental changes to the system of governance, especially concerning aspects of structuring and strengthening human resources, strengthening organizations, and improving management. This research aims to find out the optimal number of human resources and fleets to bear the workload that is in the Department of Environment and Cleanliness of Pekanbaru City. To overcome the problem of workload that occurred in the Waste Management Sector of the City Environment and Hospital Office, the qualitative method was used in this study. This method will provide information about the allocation of human resources and facilities and infrastructure to complete the existing workload. From the research conducted, it can be concluded that the waste in Pekanbaru City still cannot be transported properly due to the lack of the number of transport officers and garbage transport fleets owned by the Pekanbaru City Environment and Hygiene Agency especially in the Field of Waste Management. The high number of waste generation in the city of Pekanbaru is not in accordance with the number of officers and transport fleets, so that the garbage problems in the city of Pekanbaru still cannot be handled properly.Keywords: Workload Analysis, Human Resources, garbage.